Identification of Risk Factors for Work Stress Field Workers in Oil and Gas Industry: Literature Review - Bram Sinatra Napitupulu; Baiduri Widanarko (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Work-related stress is a significant issue in the oil and gas industry, where workers often face high-risk environments and heavy workloads. Factors such as age, length of service, type of work, and interpersonal conflicts frequently cause stress, which can affect workers' mental health and performance. Objective: This study aims to identify and analyze the risk factors of work-related stress in the oil and gas sector and provide recommendations for improved stress management. Method: This research was conducted using a literature review method, analyzing previous studies related to work-related stress among oil and gas workers. Data were collected from relevant quantitative and cross-sectional studies, involving variables such as age, length of service, workload, role conflict, and leadership. Results: The literature review shows that age, length of service, type of work, workload, and interpersonal conflict significantly relate to workers' stress levels. Interpersonal conflict is the most influential factor, while organizational support, good leadership, and work-life balance policies help reduce stress levels. Conclusion: Effective interventions in stress management, such as employee wellness programs, improved workplace safety, and work-life balance policies, are essential in this sector. Early detection of stress sources is also crucial to maintaining workers' mental health and increasing productivity in the oil and gas industry.